2021
DOI: 10.1021/jasms.1c00137
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Registration of the Mass Spectrometry Imaging Data of Sagittal Brain Slices to the Reference Atlas

Abstract: The registration of the mass spectrometry imaging (MSI) data with mouse brain tissue slices from the atlases could perform automatic anatomical interpretation, and the comparison of MSI data in particular brain regions from different mice could be accelerated. However, the current registration of MSI data with mouse brain tissue slices is mainly focused on the coronal. Although the sagittal plane is able to provide more information about brain regions on a single histological slice than the coronal, it is diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Data from other modalities provide complementary molecular or spatial information, which may be used to enhance the quality of MSI data or provide additional insights using more targeted analytical tools. MSI data have been coupled with histology, [ 91 , 133 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ] fluorescence microscopy, [ 188 , 189 , 190 , 191 ] Allen brain atlas, [ 107 , 192 ] topology, [ 193 , 194 , 195 ] electron microscopy, [ 196 , 197 ] Raman spectroscopy, [ 198 , 199 , 200 , 201 ] infrared spectroscopy, [ 202 ] magnetic resonance imaging, [ 93 , 203 ] and microsampling LC‐MS/MS analysis of proteins, transcripts, and genes. [ 164 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ] In these studies, computational approaches have been used for registration of the multimodal data.…”
Section: Computational Methods For Msi Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Data from other modalities provide complementary molecular or spatial information, which may be used to enhance the quality of MSI data or provide additional insights using more targeted analytical tools. MSI data have been coupled with histology, [ 91 , 133 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ] fluorescence microscopy, [ 188 , 189 , 190 , 191 ] Allen brain atlas, [ 107 , 192 ] topology, [ 193 , 194 , 195 ] electron microscopy, [ 196 , 197 ] Raman spectroscopy, [ 198 , 199 , 200 , 201 ] infrared spectroscopy, [ 202 ] magnetic resonance imaging, [ 93 , 203 ] and microsampling LC‐MS/MS analysis of proteins, transcripts, and genes. [ 164 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ] In these studies, computational approaches have been used for registration of the multimodal data.…”
Section: Computational Methods For Msi Data Analysismentioning
confidence: 99%
“…For example, the profiles of hippocampus, central canal, and cerebral peduncle in brain samples have been used to aid image registration of MSI data to the Allen brain atlas and histology images. [ 107 , 185 ] In the absence of fiducial markers, the geometrical information from the whole image may be used to facilitate registration. In conventional metrics for evaluating image similarity, such as mutual information, input images are required to have the same dimensionality.…”
Section: Computational Methods For Msi Data Analysismentioning
confidence: 99%
“…Tian et al . [80] described a pipeline for automatic registration of mouse sagittal DESI‐MSI data to the Allen Brain Atlas, providing annotation of detected molecular species by brain region without the need for a histology expert. Recent developments also include the use of nonlinear registration methods to correct local geometric alterations.…”
Section: Multimodal Msi For Single‐cell Measurementsmentioning
confidence: 99%
“…Computational methods are also critical in MS imaging due to the high complexity and dimensionality of the data. Huang et al developed a method for automatic registration of the MSI data for sagittal brain sections to a reference atlas by adding auxiliary lines between brain regions . Dong, Zhao, Cai et al developed a flexible unsupervised deep learning model for analyzing metabolic heterogeneity based on MSI data without prior knowledge of histology .…”
Section: Instrumentationmentioning
confidence: 99%
“…Huang et al developed a method for automatic registration of the MSI data for sagittal brain sections to a reference atlas by adding auxiliary lines between brain regions. 28 Dong, Zhao, Cai et al developed a flexible unsupervised deep learning model for analyzing metabolic heterogeneity based on MSI data without prior knowledge of histology. 29 For tackling a similar challenge, Huang, Zeng, Wu et al reported an information entropy-based strategy for dimension reduction and better data visualization.…”
mentioning
confidence: 99%